Pengabdian Kepada Masyarakat Uji Kompetensi Kejuruan Jurusan Teknik Otomotif di SMK Rigomasi Bontang - Yano Hurung Anoi (Jurnal Pengabdian Ahmad Yani, 2021)
Abstract The skill competency test activity is a very strategic educational activity to reveal student competency achievements. Competence is an ability to carry out or perform a job or task based on skills and knowledge and supported by the work attitude required by the job. The purpose of the competency test is to measure students' cognitive abilities or to test the process objectives of a program by using the practicum test assessment format or observing activities of groups or individuals. The method of implementing the activities is carried out in several stages including the preparation stage, the implementation stage and the implementation results stage. The results of the implementation of Community Service activities in the form of competency tests in the field of expertise have been carried out well with indicators of satisfaction with these activities, namely (1). quite good coordination between Rigomasi Vocational School and STTI Bontang in organizing competency test activities so that competency test activities run smoothly, (2). Rigomasi Vocational High School students in general can work on the questions given in the competency test well, so it is hoped that the skills they have can be put into practice in the real world of work. Keywords: competency test; students; Rigomasi Vocational High School.